Strategic Role of Pension Fund Administrators in Motivating Contributors’ Interests in the Nigerian Pension Scheme - JEVWEGAGA, Helen; IBIDUNNI, Ayodotun Stephen; AKINNUSI, Maloma David (Journal of Advanced Research in Law and Economics, 2020)
The focus of this research was to determine the strategic role of Pension Fund Administrators (PFAs) in motivating contributors’ interests in the Nigerian pension scheme. Effort was made to ascertain the extent of payment of pension benefits to contributors as and when due and to also ascertain the level of payment of interests and bonuses to the contributors on funds invested as and when due. The study utilized structured questionnaire to obtain data from active Retirement Savings Account (RSA) holders and pensioners based on their perceived interests on pension matters in Nigeria. A total of 168 RSA holders and 149 pensioners were purposively and randomly selected for the study within the South-West region of Nigeria. From the application of the regression technique, the data analysis revealed that prompt payment of pension benefits and contributions by PFAs significantly influence contributors’ motivation in the pension scheme. Also, the result showed that payment of interests and bonuses on pension funds invested has a significant effect on the contributors’ satisfaction with the pension scheme. Therefore, the study recommended that PFAs should devise means to educate the beneficiaries on the modalities for calculating pension allowances so as to improve their customer service initiatives for increased market share, and to regularly update the RSAs of beneficiaries with the interests and other bonuses from pension investments.